The Influence of Economic Literacy and Family Environment on Students' Entrepreneurial Interest - Af Idah, Sakinatul; Mustika Dewi, Retno (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
Entrepreneurship is a viable solution to address economic challenges, so fostering entrepreneurial interest among the younger generation is crucial. In actuality, younger people aren't all that interested in entrepreneurship right now. Employing quantitative techniques with causal associative types, this study seeks to examine how students' interest in entrepreneurship is influenced by economic literacy and their familial environment. Saturated sampling technique was used by taking the entire population of eleventh grade Economics students at Khadijah High School in Surabaya, totaling 92 people. This research provides results that partially economic literacy does not have a significant effect on students' entrepreneurial interest, whereas the family environment has a significant influence on students' entrepreneurial interest. Simultaneously, economic literacy and the family environment together influence entrepreneurial interest. These findings suggest that the family environment has a greater impact than economic literacy in shaping students' entrepreneurial interest